Habitat context affects sediment nitrogen burial by restored Eastern Oyster reefs - Anne Margaret H. Smiley; F. Joel Fodrie; Jonathan H. Grabowski; Antonio B. Rodriguez; Suzanne P. Thompson; Michael F. Piehler (PLoS ONE, 2026)
Oysters perform essential functions in estuarine environments. Reef restoration has recently become the subject of significant attention to reestablish populations after historic losses and to restore valuable ecosystem functions and services, including nitrogen removal. Nitrogen burial in oyster reef sediments may be an important nitrogen sink, but direct measurements are lacking. We assayed sediments from 11- to 14-year-old restored oyster reefs in three representative habitat contexts in a temperate estuary on the US Atlantic Coast. Elemental analysis of deep core sediments revealed that nitrogen burial rates ranged between 1.02 and 14.7 g N m -2 y -1 and generally scaled positively with reef relief and density. Intertidal flat reefs exhibited the greatest relief values, densities, and nitrogen burial rates. Subtidal flat reefs produced the lowest relief values and burial rates. Intertidal fringing reefs exhibited the lowest mean carbon:nitrogen ratio, 15.5 ± 1.3—burying proportionally more nitrogen than reefs in other habitat contexts. Using avoided cost methods, the value of nitrogen burial by oyster reefs in all habitat contexts ranged from $270 to $3,900 US dollars (USD) per hectare per year with an average of $1,700 USD per hectare per year. Integrating this figure into current estimates of nitrogen removal ecosystem services would increase the value 25–42%. Our findings suggest that specific site selection for restored and protected reefs can maximize nitrogen removal through multiple mechanisms, including burial. Providing empirical measurements of ecosystem function and estimates of economic value can inform site selection and design of restored oyster reefs to maintain water quality.